Starting aripiprazole long-acting-once-a-month early in treatment: why, how and for whom? Expert consensus and practical recommendations by a panel of Italian clinicians. (1st November 2016) - Amodeo, Giovanni; Candiracci, Chiara; Capecci, Ilaria; De Filippis, Sergio; Giuliani, Sonia; Guerani, Giorgio; Tomasetti, Carmine; Villari, Vincenzo; Fagiolini, Andrea
ABSTRACT: Introduction : Aripiprazole long acting once-monthly (AOM) is approved for the treatment of schizophrenia in adults. Despite recent evidence of AOM efficacy in the acute treatment of schizophrenia, it is recommended that AOM should be started once the acute symptoms are controlled and patients are stabilized. However, there currently are no definitive guidelines exactly describing when a patient is to be considered stabilized enough to start AOM and which the patients are for whom an early AOM start is to be preferred. Areas covered : A panel of Italian clinicians experienced with real world use of AOM met to discuss the scenarios where an early (i.e., immediately after controlling the acute symptoms) start of AOM may be suggested. Real life clinical experiences were shared and a consensus was reached. Expert opinion : There are cases when the risks/benefits ratio suggests to start AOM early, i.e. immediately after the acute symptoms have been stabilized, as opposed to starting it several days/weeks after the stabilization of acute symptoms. Clinical pearls, guidelines and opinions are provided.